School based assessment of the secondary school integrated curriculum (KBSM) of music education in Peninsular Malaysia / Lee Soo Mei @ Jake Lina Lee - Lee , Soo Mei @ Jake Lina Lee (2020)
The purpose of this study is to identify differences of attitude (affective, cognitive, evaluation and conation) and the perception (knowledge, satisfaction, understanding, experience and effective) of music teachers toward the School Based Assessment (SBA) of the Secondary School Integrated Curriculum (KBSM) in the lower secondary public schools in Peninsular Malaysia in terms of gender and teaching experience demography. This study also identifies the opinion of the stakeholders (education officers, examination syndicate officer, principle, parents, teachers and students) toward the implementation of SBA. The study also aims to identify the students’ musical ability and band achievement based on the Standard Performance Document provided by the Examination Syndicates of Malaysia. This study employed a mixed-method, where quantitative data was collected by the first cohort of students (n=238) from eight public lower secondary schools over Peninsular Malaysia that responded in the band-achievements based on the Standard Performance Document prepared by the Examination Syndicates of Malaysia. In this study, in-service teachers (n=29) responded via a survey instrument consisting of 51 scaled item and the data were analyzed using SPSS software. The qualitative data was collected using interviews, analysis of documents and data, transcribed and analyzed using Atlas. ti software. This study showed that majority of the respondents welcomed the implementation of SBA. However, it effectiveness depends on the emphasis on the quality assurance (monitoring, standardize, mentoring and detection). These are aligned with the desires of the National Education Philosophy of Malaysia.